A critical analysis of development NGO programmes in rural areas: a case study of East Cape Agricultural Research Project in South Africa - Sanyangore, Agnes (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
For a number of decades now, development non-governmental organisations (DNGOs) have been central to the world-wide development system which involves funding from international donors. Overall, DNGOs rely quite fundamentally on their donors for organisational sustainability, such that upward accountability to donors is inevitable. At the same time, as development agents, DNGOs are often celebrated for the deep participatory methodologies used when engaging with the beneficiaries of their programmes, leading to significant downward accountability "“ as least potentially. Often, for DNGOs, an awkward tension between upward and downward accountability exists. This thesis considers this tension by examining a DNGO in South Africa, namely, the East Cape Agricultural Research Project (ECARP), which focuses on questions around land redistribution. ECARP works with farm labourers and dwellers on commercial farms and small-scale farmers on redistributed farms. In the context of a broader understanding of ECARP's mission, capacities and programmes, the thesis looks specifically at ECARP's food security and sovereignty programme amongst small-scale farmers on redistributed farms. By drawing upon Interface theory, the thesis discusses in detail the diverse manner in which ECARP uses participatory methodologies in this particular programme. The thesis concludes that there is a reasonable degree of downward accountability in this programme, but that this does not distract from the fact that ECARP remains within the tension-riddled space marked by dual demands for accountability.
Keywords: East Cape Agricultural Research Project; Non-governmental organization -- South Africa -- Eastern Cape; Rural development -- South Africa -- Eastern Cape; Agricultural development projects -- South Africa -- Eastern Cape; Land reform -- South Africa -- Eastern Cape; Land tenure -- South Africa -- Eastern Cape